The Effects of Different Stages of Mindfulness Meditation Training on Emotion Regulation - Zhang, Qin; Wang, Zheng; Wang, Xinqiang; Liu, Lei; Zhang, Jing; Zhou, Renlai (Frontiers in Human Neuroscience, 2019)
This study examined mood enhancement effects from four-week focusing attention (FA) meditation and four-week open monitoring (OM) meditation in an eight-week mindfulness training program designed ¬for ordinary individuals. 40 participants were randomly assigned to a training or a control group. All participants were asked to perform cognitive tasks and subjective scale tests at three-time points (pre-, mid, and post-tests). Compared with the participants in the control group, the meditation training group showed significantly decreased anxiety, depression and emotional rumination scores, significantly increased mindfulness scores, and significantly reduced reaction times for the Stroop task in the incongruent condition. The present study demonstrated that eight-week mindfulness meditation training could effectively enhance the level of mindfulness and improve emotional states. Moreover, FA meditation could partially improve individual levels of mindfulness and effectively improve mood, while OM meditation could further improve individual levels of mindfulness and maintain a positive mood.